Human MHC class I molecule, HLA-A2.1, mediates activation of CD8+ T cell IFN-γ production and the T cell-dependent protection against reactivation of cerebral Toxoplasma infection - Mani, Rajesh; Abdelaziz, Mohamed H.; Michelon, Alexandra; Suzuki, Yasuhiro (Frontiers in Immunology, 2022)
To examine whether the HLA-A2.1, one of the most common MHC class I molecules in humans, activates the protective immunity against reactivation of cerebral infection with Toxoplasma gondii, HLA-A2.1-transgenic and wild-type (WT) mice were infected and treated with sulfadiazine to establish chronic infection in their brains. One month after discontinuation of sulfadiazine, which initiates reactivation of the infection, mRNA levels for tachyzoite (the acute stage form)-specific SAG1 and numbers of the foci associated tachyzoites were significantly less in the brains of the HLA-A2.1-transgenic than WT mice. Greater numbers of IFN--producing CD8+ T cells were detected in the spleens of infected transgenic than WT mice, and CD8+ T cells from the former produced markedly greater amounts of IFN- than the T cells from the latter in response to tachyzoite antigens in vitro. When their CD8+ T cells were systemically transferred to infected immunodeficient NSG mice expressing the HLA-A2.1, the CD8+ T cells from HLA-A2.1-transgenic mice inhibited reactivation of the cerebral infection in the recipients more efficiently than did the WT T cells. Furthermore, the inhibition of reactivation of the infection by CD8+ T cells from the transgenic mice was associated with increased cerebral expression of IFN- and effector molecules against tachyzoites in the recipients when compared to the WT CD8+ T cell recipients. Thus, the human HLA-A2.1 is able to effectively activate IFN- production of CD8+ T cells against T. gondii tachyzoites and confer a potent protection against reactivation of cerebral infection with this parasite through the CD8+ T cells activation.